La rentabilidad salarial de la educación universitaria en España: ¿existen diferencias por áreas geográficas? - Aguilar Sabán, José Tomás (My University, 2022)
This Final Degree Project aims to analyze the differences between the salary profitability that individuals receive, according to their educational level, in the various Spanish regions, distinguishing between the 7 NUTS recognized by the European Union. We will focus on Higher Education, for its evident relevance in salary performance, distinguishing individuals according to whether they are Graduates or Graduates. We will use for this the microdata of the Salary Structure Survey (EES) of 2018, carried out by the National Institute of Statistics (INE), which provides us with the necessary information to be able to carry out the econometric analysis, on which our Work is based. In relation to the econometric analysis, we have carried out for each NUTS a function of salary gains, based on the salary function model already proposed by Mincer, in order to observe the incidence of the educational level in the hourly salary of individuals, depending on the Spanish region in which they are located. This work is the Final Degree Project of my studies at the University of Malaga, in the branch of Business Administration and Management. Born from my curiosity to investigate the incidence of university education in the Spanish regions.
The salary profitability of university education in Spain: are there differences by geographical areas?
Keywords: Salarios; Enseñanza superior; Grado en Administración y Dirección de Empresas - Trabajos Fin de Grado; Adminsitración y Dirección de Empresas - Trabajos Fin de Grado; Rentabilidad salarial; Educación universitaria